1993
DOI: 10.1128/mcb.13.12.7725
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the L-type pyruvate kinase gene glucose response complex.

Abstract: L-type pyruvate kinase (L-PK) gene expression is modulated by hormonal and nutritional conditions. We have previously shown that the glucose/insulin response element (GIRE) of the L-PK gene is built around two noncanonical E boxes (element IA) that cooperate closely with a contiguous binding site (element L3). We present in this report the identification of proteins that interact with both elements. The L3 site binds hepatocyte nuclear factor 4 (HNF4)-and COUPITF-related proteins. In fibroblasts, the overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
1
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 32 publications
0
110
1
1
Order By: Relevance
“…A number of studies have established that FKHR activates the transcription of gluconeogenic enzymes in the absence of insulin and inhibits the transcription in the presence of insulin. On the other hand, HNF-4 positively regulates the genes involved in glucose transport and glycolysis (4,6). Here, we provided a novel mechanism that insulin reversed the repression of HNF-4 transcriptional activity by FKHR.…”
Section: Effects Of Insulin On the Repression Of Hnf-4 Transactivatiomentioning
confidence: 81%
“…A number of studies have established that FKHR activates the transcription of gluconeogenic enzymes in the absence of insulin and inhibits the transcription in the presence of insulin. On the other hand, HNF-4 positively regulates the genes involved in glucose transport and glycolysis (4,6). Here, we provided a novel mechanism that insulin reversed the repression of HNF-4 transcriptional activity by FKHR.…”
Section: Effects Of Insulin On the Repression Of Hnf-4 Transactivatiomentioning
confidence: 81%
“…The promoter (-183 to +11) contains binding sites for HNF-1, NF-I, HNF-4, upstream stimulating factor (USF)-related proteins and L5-binding factors (Figure 1) [80][81][82][83]. The HNF-4 site also binds chicken ovalbumin upstream promoter-transcription factor (COUP-TF)I and COUP-TFII [84]. The binding of HNF-4 apparently stabilizes NF-I binding [80].…”
Section: Tissue-specific Controlmentioning
confidence: 99%
“…ChREBP is reported to bind to L-III as a heterodimer with Max-like protein X. It has been widely accepted that HNF4␣ is involved in transcriptional activation of the L-PK gene, because reporter gene assays and binding assays showed that HNF4␣ stimulates the L-PK promoter activity by binding to the L-IIB element (10,13,24). However, we suspected an alternative mechanism, because NF1 family members also bind to the L-IIB element as well as the accessory element in the S 14 gene, whereas HNF4␣ does not bind to this element in the S 14 gene (25).…”
mentioning
confidence: 99%